2022
DOI: 10.1002/admi.202201400
|View full text |Cite
|
Sign up to set email alerts
|

Rational Construction of Z‐Scheme Charge Transfer Based on 2D Graphdiyne (g‐CnH2n−2) Coupling with Amorphous Co3O4 Quantum Dots for Efficient Photocatalytic Hydrogen Generation

Abstract: A novel Co3O4 quantum dots (CQDs)/2D graphdiyne (GDY) Z‐scheme heterojunction is fabricated by cross‐coupling reaction and electrostatic self‐assembly methods. GDY with the features of 2D porous structures has not only conducted the adsorption of dye molecules but also CQDs is facile to be anchored on the surface. Additionally, the construction of Z‐scheme heterojunction is conductive to conquer the shortcomings of easy agglomeration and poor dispersion for CQDs. The maximum photocatalytic hydrogen generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In addition, a distinct absorption band can be observed at 2190 cm À 1 due to the stretching vibration of C�C. [35] The Raman spectrum of GDY (Figure 2F) shows two strong peaks (1363.83 cm À 1 and 1566.94 cm À 1 ) and two weak peaks (1999 cm À 1 and 2178 cm À 1 ). The two strong peaks are attributed to the respiration vibration of the sp 2 carbon domain of the aromatic ring (D band) structure (1363.83 cm À 1 ).…”
Section: Xrd Ft-ir and Raman Spectra Analysismentioning
confidence: 99%
“…In addition, a distinct absorption band can be observed at 2190 cm À 1 due to the stretching vibration of C�C. [35] The Raman spectrum of GDY (Figure 2F) shows two strong peaks (1363.83 cm À 1 and 1566.94 cm À 1 ) and two weak peaks (1999 cm À 1 and 2178 cm À 1 ). The two strong peaks are attributed to the respiration vibration of the sp 2 carbon domain of the aromatic ring (D band) structure (1363.83 cm À 1 ).…”
Section: Xrd Ft-ir and Raman Spectra Analysismentioning
confidence: 99%
“…The molecule (small molecules or macromolecules)-modified GDY are usually fabricated by solution blending via robust 𝜋-𝜋 interaction (e.g., ferrocene (Fc)modified GDY, [55] and hemin/GDY [56] ), and van der Waals interaction (e.g., poly(vinylidene fluoride) (PVDF)/GDY, [57] and polyvinylpyrrolidone (PVP)/GDY [58] ). The interface engineering of GDY modified by other nanostructures (0D, 1D, or 2D morphology) is also frequently employed for the construction of GDY-based heterostructures by versatile strategies, such as in situ cross-coupling reaction using HEB as a monomer (e.g., metal (Cr, Mn, Mo, W, and Re) SA/GDY, [59] and 1D Cu 0.95 V 2 O 5 nanorod (NR)@GDY [60] ), and self-assembly (e.g., Co 3 O 4 QD/GDY, [61] and MXene Ti 3 C 2 T x NS/GDYO [62] ). The schematic illustrations of the representative functional GDY nanoarchitectures [69,[88][89][90][91] are provided in Figure 2.…”
Section: Controlled Synthesismentioning
confidence: 99%
“…[143] However, the reported current density (j) of 2D GDY in HER reaction is still poor (< 0.2 A cm −2 ), mainly attributed to the relatively low intrinsic catalytic active sites. [127] In recent years, functional GDY nanoarchitectures that GDY bonds with heteroatoms to generate featured chemical bonds such as C−N, [144] C−Cu, [145] C−Pt, [146] and C−Pd bonds, [147] or hybridizes with other nanostructures, such as, 0D SAs or QDs, [61] 1D NWs, [81] and 2D NSs [148] to form a variety of heterojunctions, have shown remarkably boosted electrochemical catalytic performance. For example, in 2021, Wang et al [149] reported a sequential strategy for the co-doping of B and N heteroatoms into GDY, which showed that a certain sp-N doping could reduce the HER overpotential, and the subsequent incorporation of B atoms further enhanced the j due to the synergistic effect of chemical and electronic couplings on proton adsorption/reduction kinetics.…”
Section: Hermentioning
confidence: 99%
“…In addition, the greater the absolute value of zeta potential, the better the stability of photocatalyst in solution. [34][35][36] At the same time, the larger the zeta potential is, the greater the electrostatic repulsion between particles, which results in a great inhibition on aggregation and sedimentation. Therefore, when the particles can maintain good dispersion in solution, it also indicates that they have good stability.…”
Section: Zeta Potentials Analysismentioning
confidence: 99%